Wpływ parametrów zakłócających na pracę skrzyni biegów wyposażonej w przekładnię CVT - Pawelski, Zbigniew; Radzymiński, Bartosz (Wydawnictwo Politechniki Łódzkiej, 2015)
The paper presents mechanical scheme of transmission from Nissan Micra vehicle equipped with a push belt. For the tested gearbox test bench has been prepared in which it was possible to simulate the load conditions and adjust pressures responsible for the transmission operation through open and closed systems using PID controllers.
Artykuł zamieszczony w : „Problemy rozwoju maszyn roboczych” XXVIII Konferencja Naukowa Zakopane 2015 (Materiały konferencyjne wydane w serii Monografie PŁ)
Keywords: skrzynia biegów; przekładnia CVT; parametry zakłócające; obciążenie